Rancang Bangun Aplikasi Sistem Penggajian Karyawan di Yayasan Mitra Tani Mandiri Kabupaten Nagekeo Berbasis Web Menggunakan Metode Waterfall - Rero, Aukladia Fitri; Faizah, NM; Nurcahyo, Widyat (Yayasan Kawanad, 2024)
This study aims to design and develop the application of web -based employee payroll systems at Mitra Tani Mandiri Foundation using the Waterfall method. Efficient and accurate payroll process is a crucial factor in organizational management, especially in Mitra Tani Mandiri Foundation which has employees with various responsibilities and roles. The waterfall method was chosen because of the systematic development stage, starting from the needs analysis to the maintenance stage. The needs analysis phase involves collecting data related to the existing payroll process, employee needs, and management requirements. The design stage includes planning an intuitive user interface, structured database design, and a comprehensive system implementation plan. Implementation is done by building applications according to the specifications that have been designed, involving programming, developing databases, and integration of various components. The testing phase aims to ensure the application is functioning properly, accurately, and according to purpose. The results of this study are web -based payroll systems applications that are expected to improve the efficiency of the payroll process, reduce the potential for human errors, and provide transparency of salary information to employees. The implementation of this application is expected to have a positive impact on the management of human resources and the overall operations of the foundation